2021
DOI: 10.1016/j.biopsych.2020.06.031
|View full text |Cite
|
Sign up to set email alerts
|

Four Deep Brain Stimulation Targets for Obsessive-Compulsive Disorder: Are They Different?

Abstract: Deep brain stimulation (DBS) is a promising therapeutic approach for patients with treatmentresistant obsessive compulsive disorder (OCD), a condition linked to abnormalities in corticobasal ganglia networks. Effective targets are placed in one of four subcortical areas with the goal of capturing prefrontal, anterior cingulate, and basal ganglia connections linked to the limbic system. These include the anterior limb of the internal capsule, the ventral striatum, the subthalamic nucleus, and a midbrain target.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(56 citation statements)
references
References 93 publications
3
53
0
Order By: Relevance
“…In the following years, different nuclei adjacent to the ALIC, including the ventral striatum (VS) containing the nucleus accumbens (NAc) as well as the bed nucleus of the stria terminalis (BNST), have been proposed as key regions for successful DBS (18,19). Through empiric evidence from DBS in movement disorders, other brain targets such as the subthalamic nucleus (STN), the inferior thalamic peduncle and the superolateral branch of the medial forebrain bundle (MFB; later referred to as ventral tegmental area projection pathway (20) or midbrain target (21)) have been successfully targeted in OCD (3,22,23). Remarkably, modulation of these distinct subcortical targets (Figure 1) all show the potential to improve obsessions and compulsions, pointing towards a common network responsible for clinical efficacy.…”
Section: From Focal Targets To Interconnected Networkmentioning
confidence: 99%
See 2 more Smart Citations
“…In the following years, different nuclei adjacent to the ALIC, including the ventral striatum (VS) containing the nucleus accumbens (NAc) as well as the bed nucleus of the stria terminalis (BNST), have been proposed as key regions for successful DBS (18,19). Through empiric evidence from DBS in movement disorders, other brain targets such as the subthalamic nucleus (STN), the inferior thalamic peduncle and the superolateral branch of the medial forebrain bundle (MFB; later referred to as ventral tegmental area projection pathway (20) or midbrain target (21)) have been successfully targeted in OCD (3,22,23). Remarkably, modulation of these distinct subcortical targets (Figure 1) all show the potential to improve obsessions and compulsions, pointing towards a common network responsible for clinical efficacy.…”
Section: From Focal Targets To Interconnected Networkmentioning
confidence: 99%
“…The authors observed a significant positive correlation between clinical improvements and the proximity ratio in favor of the MFB compared to the ATR. We note the nomenclature and conceptualization of this fiber tract identified as MFB, has since evolved (21) and that the original authors now refer to this structure as ventral tegmental area projection pathway (vtaPP) (20) while others referred to it as a midbrain projection (21) (see below for a detailed discussion).…”
Section: Connectomic Studies Of Deep Brain Stimulation For Ocdmentioning
confidence: 99%
See 1 more Smart Citation
“…There is substantial confusion in the dMRI literature regarding the position of the medial forebrain bundle (Haber et al, 2020). This bundle does not ascend into the internal capsule; instead, it remains ventrally positioned until reaching its targets in the frontal lobe.…”
Section: Medial Forebrain Bundlementioning
confidence: 99%
“…However, because of the previously mentioned issues with tracking brainstem fibers, there is a widespread misunderstanding of the types of connections DBS in different locations can affect. DBS of the internal capsule is not capturing the medial forebrain bundle, and therefore not capturing dopaminergic axons (Coenen et al, 2009;Haber et al, 2020).…”
Section: Medial Forebrain Bundlementioning
confidence: 99%